GAMBARAN KEJADIAN EKSTRAPIRAMIDAL SINDROM PADA PASIEN TERAPI ANTIPSIKOTIK TIPIKAL DI RUMAH SAKIT JIWA ACEH - Vivi Asfianti; Alfi Syahfitri; Zuhairiah NST (FORTE JOURNAL, 2022)
The use of antipsychotics in schizophrenic patients often causes side effects in the form of Extra Pyramidal Syndrome (EPS), namely the presence of uncontrolled muscle movement disorders such as seizures, shaking and so on. The incidence of EPS is more common with the use of typical antipsychotics than atypicals. This study aims to see the incidence of EPS in inpatients with schizophrenia at the Aceh Mental Hospital located in Banda Aceh in 2020. The population in this study were all inpatients who were given typical antipsychotics. While the research sample was 399 samples collected from medical record data of inpatients in 2020, so the study was retrospective with a cross sectional approach. Data collected in the form of patient identity (gender, age), drug therapy (typical antipsychotics) and the incidence of EPS. The results showed that schizophrenic patients who received typical antipsychotic therapy who were hospitalized at the Aceh mental hospital in 2020, were 324 men (81.2%) and 75 women (18.8%), with the highest age range being at 36-45 years amounting to 202 people (50.6%). Typical antipsychotic therapy used in the form of combination of typical-typical and typical-atypical drugs, namely clozapine-trifluperazine (40.6%), chlorpromazine-risperidone (20.3%), haloperidol-chlorpromazine-trifluperazine (16%), haloperidolchlorpromazine (7%), and haloperidol-trifluperazine (5%). The incidence of EPS that occurred was 113 people (28.3%), with the highest number of EPS occurring from the administration of haloperidol-chlorpromazine-trifluperazine combination antipsychotic therapy, which was 61 people (15.3%).